Facilities and services of postexposure prophylaxis in anti-rabies clinics: A national assessment in India - Mysore Kalappa Sudarshan; Ravish Shankaraiah Haradanhalli (Wolters Kluwer Medknow Publications, 2019)
Background: The rabies postexposure prophylaxis (PEP) is provided through anti-rabies clinics in the country. It was considered important to assess their facilities under a nationwide multi-centric survey. Objectives: The objective of this study is to assess the facilities available for PEP at the anti-rabies clinics and to ascertain the PEP provided at the anti-rabies clinics. Methods: The cross-sectional assessment was made from May 2017 to January 2018 in selected seven states of India. Thirty-five anti-rabies clinics from both Government and private; urban and rural areas from the states were assessed by an expert team using a pretested checklist for facilities and services available for PEP. Results: On an average, 10 new animal bite cases were attended at each anti-rabies clinic per day. The cold chain facilities for rabies biologicals were satisfactory. The facilities for wound washing (54.3%) and the use of antiseptics to animal bite wounds were not adequate. Rabies vaccines were administered by intramuscular in 54.3% and by intradermal route in 45.7% of the cases. The vaccine stock-outs were reported only in the government sector (18.5%). The type of rabies immunoglobulin (RIG) used was equine (63.2%) and human (36.8%); given free of cost in 40% of Anti rabies clinics. The local wound infiltration of RIG was in practice at 58.6% of anti-rabies clinics. The stock-out of RIG was more in private (50%) hospitals than in Government (40.7%) hospitals. Conclusion: The facilities available for PEP at the anti-rabies clinics were inadequate and have to be improved across the country.